Students' Mathematical Literacy in Solving PISA Model Questions: A Case Study of Systematic and Intuitive Cognitive Style - Utama, Dikey Putra; Budiarto, Mega Teguh; Masriyah (Indonesian Journal of Mathematics Education, 2024)
This research is a qualitative descriptive study that aims to describe the mathematical literacy of high school students with a systematic and intuitive cognitive style in solving PISA model questions. The cognitive style test, cognitive style inventory, and mathematics ability test were used to select research subjects. One student with a systematic cognitive style and one with an intuitive cognitive style were selected with equivalent mathematical abilities and the same gender. The results of the mathematical literacy test and test-based interviews were used to collect data on students' mathematical literacy. Time triangulation was used to test the credibility of the findings obtained. Data analysis techniques include data reduction, presentation, and drawing conclusions. The research results show that in formulating problems, systematic students identify the information obtained from the two questions in more detail and are more careful in understanding the questions, while intuitive students identify the necessary information to solve the problem in general. In applying problems, systematic students design and use strategies to find solutions, identifying known information from the problem first, while intuitive students create and use strategies to find solutions and solve problems using the concept of comparison. For the interpreting aspect, the two students reinterpreted the mathematical results they obtained into contextual problems, stated the truth of the answers they obtained, and provided arguments to support their answers.